The The Factors Affecting on Lao’ Labor Migration to Abroad - SK, Jai (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
The research of the factors affecting on Lao’ labor migration to abroad aims to study: 1. the factors that affects Lao labor migration to Thailand during 2010-2024. Using time series data from 2010-2024. The study uses descriptive statistics to analyze the factors to labor migration and quantitative analysis using multiple regression equations with the Ordinary Least Squares (OLS) method to study the factors that affects Lao labor migration to Thailand. The findings reveal that the number of Lao workers migrating to Thailand has fluctuated over time, closely associated with the domestic economic conditions in Laos. During the study period, the total number of Lao labor reached 709,391 people, average 47,293 people per year. For the results of the test of the factors affecting on Lao labor migration to Thailand, it was found that there are three factors such as the wage in Thailand, Inflation rate in Lao PDR and policy on labor collaboration between two countries Lao PDR and Thailand that are positively correlated with the number of Lao labor migration to Thailand. with statistical significance at the level of 0.01 for all factors. For Dubin-Watson d-statistic 2.01 without autocorrelation when consider from Probability (F-Statistic) equal 0.0003 which is less than 0.01 confirming the overall significance of the model